IPv6 in low-power transceivers for wireless sensor networks - Lansang, Jeric Francis A. (2007)
The application of wireless sensor networks have become widespread, emerging from military operations and now covering medical, structural, environmental, and management applications. With these variety of uses, wireless networks demand more reliability and connectivity, which can be provided by IPv6. IPv6 is the new version of the Internet Protocol designed as a sucessor to IPv4. The features of IPv6 make it the protocol choice for such applications, as sensor nodes can reach up to thousands in number and the demands in terms of connectivity and communication are also growing. The 128-bit address space provided by IPv6 presents a virtually unlimited addressing space, a big improvement from IPv4's 32bit address space. The goal of this project is to implement the TCP/IP stack on an 8-bit microcontroller based wireless transceiver module operating over an IEEE 802.15.4-standard based network. IPv6 technology, on top of IEEE 802.15.4 for wireless sensor networks, will provide connectivity with other IP-enabled devices and simplify adaptive routing models. Wireless sensor networks are characterized by significantly more devices than existing networks. These networks require more robust routing protocols and more address space, thus the need for IPv6. IPv6 implementation on the wireless transceivers is based on existing developements of the TCP/IP stack for memory-constrained devices. Transmission and reception of IP packets are made to comply with the IEEE 802.15.4-standard. A packet service program is developed to manage the extraction and encapsulation of the IP packet from and into the 802.15.4 frames. The implementation of IPv6 includes ICMPv6 and Neighbor Discovery.